2015
DOI: 10.1186/s12890-015-0112-1
|View full text |Cite
|
Sign up to set email alerts
|

More severe hypoxemia is associated with better subjective sleep quality in obstructive sleep apnea

Abstract: BackgroundPerceived sleep quality may play an important role in diagnosis and therapy for obstructive sleep apnea (OSA). However, few studies have assessed factors that are associated with perceived sleep quality in OSA patients. Hypoxemia depresses the central nervous system and attenuates the perceived respiratory load in asthmatic patients. This study aimed to investigate the factors related to perceived sleep quality, focusing on the role of hypoxemia.MethodsPolysomnography studies of 156 OSA patients were… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
7
0

Year Published

2016
2016
2020
2020

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(8 citation statements)
references
References 38 publications
1
7
0
Order By: Relevance
“…For the interpretation of these results, it is necessary to discuss the association of potential confounders with Poor SSQ. Although several health problems such as sleep apnoea, depression and suicide are associated to poor SSQ, 3–5 and thus are considered to be potential confounders, the present study did not measure these health problems. Therefore, our results could not provide the data for precise interpretation.…”
Section: Discussionmentioning
confidence: 94%
See 1 more Smart Citation
“…For the interpretation of these results, it is necessary to discuss the association of potential confounders with Poor SSQ. Although several health problems such as sleep apnoea, depression and suicide are associated to poor SSQ, 3–5 and thus are considered to be potential confounders, the present study did not measure these health problems. Therefore, our results could not provide the data for precise interpretation.…”
Section: Discussionmentioning
confidence: 94%
“…Subjective sleep quality (SSQ) is defined by the satisfaction of one’s overall sleep experience and is composed of sleep depth and restfulness. 1 2 Past studies have reported poor SSQ to be associated with several health problems such as sleep apnoea, 3 depression, 4 suicide, 5 obesity 6 and cardiovascular disease. 7 Sleep disturbance such as low-quality sleep may cause an increase in medical costs in cases where it accompanies other diseases.…”
Section: Introductionmentioning
confidence: 99%
“…However, CPAP treatment also did not reduce PSQI global score below 5.0, showing that the PSQI global score is dependent on more factors than REI. 2,23 The limited reduction of PSQI global score in the CPAP group may be due to low CPAP compliance in the ITT analysis. However, the PP analysis showed that when only including patients who used the MAD or CPAP more than 4 hours, more than 50% of nights, more patients using MAD than using CPAP report improved sleep quality according to the RCI (Table 3).…”
Section: Discussionmentioning
confidence: 99%
“…15,20 The patient's perceived sleep quality while using CPAP or MAD might be one such factor, but self-reported sleep quality during OSA treatment is not extensively studied. 17,23 Contrary to polysomnographic analysis of sleep quality, which shows sleep efficacy and changes in sleep stages during OSA treatment, 24,25 self-reported sleep quality shows how the patient experiences the effect of OSA treatment on sleep quality. It is currently not clear which OSA treatment is better at improving self-reported sleep quality, or how much improvement could be expected in patients with mild and moderate OSA.…”
Section: Introductionmentioning
confidence: 99%
“…The best method by which to score hypopnea events and whether or not AHI is the best parameter to measuring the severity of OSA are debatable. [35][36][37] Currently, the oxygen desaturation threshold (ODT) levels for hypopnea can be 3% or 4% based on different definitions proved by the AASM in 2013. 38 Myllymaa et al studied middle-aged subjects and found that the number of patients with AHI ≥ 15 decreased by approximately 44% when hypopnea was classified according to ODT4% (AASM 2007) instead of ODT3% (AASM 2012).…”
Section: Discussionmentioning
confidence: 99%